2020
DOI: 10.31577/ahs-2020-0021.01.0013
|View full text |Cite
|
Sign up to set email alerts
|

The measurements of saturated hydraulic conductivity of the forest floor under deciduous forest

Abstract: The aim of the paper is to present and evaluate the measured values of saturated hydraulic conductivity of organic soil horizons under deciduous forest at the examined locality Zelezna studienka. For determination of saturated hydraulic conductivity the single ring method, the falling head method and Guelph infiltrometer were used. The organic matters of forest floor come from dead plant material at various degrees of decomposition and aggregation and significantly influence the initiation processes of infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…This undoubtedly resulted also in higher saturated and unsaturated hydraulic conductivities (Ks and K) in these horizons relative to the rest of the pedon. Recent studies by Zvala et al (2020) indicated that saturated hydraulic conductivity could be very high in the forest floor, particularly in the loose litter layer typical of rich deciduous forests. The authors further emphasised that saturated hydraulic conductivity decreased in the organic horizon from top to bottom, with increasing decomposition and aggregation of organic material.…”
Section: Discussionmentioning
confidence: 99%
“…This undoubtedly resulted also in higher saturated and unsaturated hydraulic conductivities (Ks and K) in these horizons relative to the rest of the pedon. Recent studies by Zvala et al (2020) indicated that saturated hydraulic conductivity could be very high in the forest floor, particularly in the loose litter layer typical of rich deciduous forests. The authors further emphasised that saturated hydraulic conductivity decreased in the organic horizon from top to bottom, with increasing decomposition and aggregation of organic material.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of soil water retention curves θ R , α, n were computed in the model RETC version: 6.xx (van Genuchten et al 1991) The values of saturated hydralic conductivity (Ks) were determined in the authors' previous work (Zvala et al 2020). The continous polygon of SWRC was estimated in MS Excel (see Fig.…”
Section: )mentioning
confidence: 99%